Pengaruh Latihan Core Stability Dynamic dan Medicine Ball terhadap Peningkatan Kekuatan Otot Tungkai, Kekuatan Otot Perut, dan Keseimbangan - noer wachid riqzal firdauz; hari setijono (Journal of Sport Science and Education, 2018)
The development of physical condition are absolute requirement for achievement. To improve the physical condition required a training. In this research, the training in question is core stability training dynamic and medicine ball, with the aim to increase leg muscle strength, abdominal muscle strength, and balance. The purpose of this research was to analyze about: (1) The effect of core stability dynamic to enhancement leg muscle strength, abdominal muscle strength, and balance, (2) The effect of medicine ball to enhancement leg muscle strength, abdominal muscle strength, and balance. Goal of this research is the male students batch 2015, Study program Physical Education and Recreation Health STKIP PGRI Sumenep. This type of research used in this research is quantitative with quasi- experimental methods. This research design using randomize control group pretest-posttest design and analysis using anova. Data collection process with leg muscle strength test (leg dynamometer), abdominal muscle strength test (sit up), and balance test (stand stork test) when pretest and posttest. Next, the data were analyzed with the help SPSS 17.0. The result of research showed: (1) there are the effect core stability dynamic training to enhancement leg muscle strength by 7,55%, abdominal muscle strength by 11,82%, and balance by 13,17%, (2) there are the effect medicine ball training to enhancement leg muscle strength by 7,07%, abdominal muscle strength by 12,02%, and balance by 9,64%. Based analysis above, can be concluded that there enhancement leg muscle strength, abdominal muscle strength, and balance for each experimental group and the control group after being given core stability dynamic and medicine ball training seen from the t-test result. There are also differences in the effect of each workout to increase leg muscle strength, abdominal muscle strength, and balance.